Balance Sheet and Tax Aspects of Bank Debt Remission - Wiszniowski, Edward (Olsztyn Economic Journal, 2014)
Tax and balance sheet aspects of bank debt redemption. This paper is devoted to the redemption of bank liabilities, which constitutes one of the tools used by banks in the re-structuring of borrowers' debts. This is not an optimal form of shaping the relationship between the creditor and the debtor but under certain conditions, in the case of a partial redemption or redemption of a certain components of the debt, it may at least partially off-set the outstanding claims of the creditor. From the point of view of the banks, in the case of debt relief, tax laws should be considered restrictive as they contain a very limited cost catalogue qualifying them to be considered as revenue costs. From the perspective of the balance sheet, liability redemption tends to be the most neutral because the banks are obligated to perform regular write-downs on receivables. Debt redemption usually occurs after possible execution alternatives against the debtor have been pursued, and therefore when a full write-down has been created on bank's liability.